Crystal structure and electrochemical hydrogenation of HoNiIn1-xAlx (x = 0-1) solid solution - Nychyporuk, G.; Kordan, V.; Horiacha, M.; Halyatovskii, B.; Hudzo, O.; Zaremba, V.; Pavlyuk, V. (Physics and Chemistry of Solid State, 2023)
The influence of the substitution of indium by aluminum in HoNiIn compound at 873 K was investigated in the full concentration range by means of powder X-ray diffraction and EDX analysis. The formation of continuous solid solution was determined and changes of the unit cell parameters were calculated: HoNiIn1.0–0Al0–1.0 (ZrNiAl-type structure, space group P-62m, a = 0.74343(4)–0.69959(6) nm and c = 0.37472(3)–0.38289(4) nm, V = 0.17936(2)–0.16229(3) mn3). The best discharge capacity after electrochemical hydrogenation studies of HoNiIn1-xAlx solid solution is observed for battery prototypes with HoNiIn0.2Al0.8- and HoNiIn0.4Al0.6-based electrodes.